A Study of Extrovert and Introvert Personality Types on Students' Mathematical Problem-Solving Ability - Eline Yanty Putri Nasution; Rhomiy Handican; Putri Yulia (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Mathematical problem-solving ability is a crucial skill influenced by various factors, including personality types. This study aims to analyze students' mathematical problem-solving abilities based on extrovert and introvert personality types in the MBTI framework. Methodology: This research was descriptive qualitative research. Data were collected through an MBTI questionnaire to determine students' personality types and a mathematical problem-solving test to assess their abilities. The participants consisted of 11 undergraduate students from the Mathematics Education Department at Institut Agama Islam Negeri Kerinci, who were enrolled in the Mathematical Statistics course. Main Findings: Extroverted students tend to excel in understanding problems and planning solutions; however, they are more likely to overlook careful execution. In contrast, introverted students struggle with planning and do not always review the solutions they have produced. It can be concluded that extroverted students have better mathematical problem-solving abilities than introverted students in the mathematical statistics course. These results highlight the role of personality in cognitive strategies and error patterns during problem-solving. Tailored instructional approaches could help both extroverted and introverted students optimize their problem-solving abilities. The small sample size and single-institution context may limit the generalizability of these findings. Future research is recommended to expand on these insights. Novelty/Originality of this study: This study fills the gap by conducting an in-depth analysis of specific problem-solving behaviors, cognitive strategies, and error tendencies associated with extroverted and introverted students based on the MBTI framework, thereby offering a richer understanding of how personality types affect problem-solving ability.